2004
DOI: 10.1017/s007418090018218x
|View full text |Cite
|
Sign up to set email alerts
|

Coronae of Cool Stars

Abstract: Abstract. We present preliminary results of grating observations ofYY Mensae and V824 Arae by Chandra and XMM-Newton. Spectral features are presented in the context of the emission measure distributions, the coronal abundances, and plasma electron densities. In particular, we observe a coronal N/ C enhancement in YY Men believed to reflect the photospheric composition (CN cycle). Finally, we interpret line broadening in YY Men as Doppler thermal broadening in its very hot corona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This conclusion is reinforced by the much more favorable comparison of the results of the recent Chandra and XMMNewton studies of AB Dor-this work compared with that of Güdel et al (2001) and Sanz-Forcada et al (2003). Audard et al (2004), Huenemoerder et al (2003), and SanzForcada et al (2003 have recently reported, for V824 Ara, AR Lac, and AB Dor, respectively, higher values for abundances of Al, Ca, and Na than for elements with slightly higher FIPs, suggesting a schism in the strictly inverse FIP effect scheme. In particular, Sanz-Forcada et al (2003) obtained different values of Ca abundance for AB Dor, including a very high Mewe et al (1996); (2) value of ½Ca=H ¼ 0:62 derived from the high-resolution RGS spectrum.…”
Section: Coronal Abundancesmentioning
confidence: 86%
“…This conclusion is reinforced by the much more favorable comparison of the results of the recent Chandra and XMMNewton studies of AB Dor-this work compared with that of Güdel et al (2001) and Sanz-Forcada et al (2003). Audard et al (2004), Huenemoerder et al (2003), and SanzForcada et al (2003 have recently reported, for V824 Ara, AR Lac, and AB Dor, respectively, higher values for abundances of Al, Ca, and Na than for elements with slightly higher FIPs, suggesting a schism in the strictly inverse FIP effect scheme. In particular, Sanz-Forcada et al (2003) obtained different values of Ca abundance for AB Dor, including a very high Mewe et al (1996); (2) value of ½Ca=H ¼ 0:62 derived from the high-resolution RGS spectrum.…”
Section: Coronal Abundancesmentioning
confidence: 86%